Use and reporting of systematic review methodology in EFSA scientific opinions on animal health and welfare - Liesner, Johann; Ineichen, Benjamin V.; Rosso, Marianna (Frontiers in Veterinary Science, 2026)
IntroductionDespite the growing use of systematic reviews of animal studies, it remains unclear how often systematic review methodology – such as detailed search strategies, critical appraisal, and protocol registration – is applied in regulatory contexts. We aimed to assess the use and reporting quality of systematic reviews in the European Food Safety Authority’s (EFSA) Scientific Opinions on animal health and welfare.MethodsWe conducted an exploratory study comprising of a retrospective analysis of 151 EFSA Scientific Opinions. We classified the types of studies underpinning these reports, including systematic reviews, literature reviews, and other study designs. Additionally, we assessed the reporting rigor of key systematic review elements.ResultsLiterature reviews were the most common study type, present in 126 reports (83%), with 40 reports (27%) applying systematic review methods such as searching multiple databases and reporting clear research questions, inclusion criteria, and study counts. Eleven studies (27%) were explicitly labelled as systematic reviews, with their use increasing over time. Reporting quality varied: 64% listed more than one reviewer, 45% reported a risk of bias assessment, and 36% registered a study protocol.DiscussionSystematic review methodology is increasingly applied in EFSA’s Scientific Opinions on animal health and welfare. However, methodological rigor and reporting standards remain inconsistent, underscoring the need for improvement to strengthen the reliability and transparency of EFSA’s evidence base.